2022
DOI: 10.1177/10760296221107889
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection in Patients with Comorbidities: Clinical and Immunological Insight

Abstract: Aim Our study's objectives were to study the clinical and laboratory characteristics that may serve as biomarkers for predicting disease severity, IL-10 levels, and frequencies of different T cell subsets in comorbid COVID-19 patients. Methods Sixty-two hospitalized COVID-19 patients with comorbidities were assessed clinically and radiologically. Blood samples were collected to assess the T lymphocyte subsets by flow cytometry and IL-10 levels by ELISA. Results The most common comorbidities observed in COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Announced by the World Health Organization in January 2020 as a global health emergency and in March 2020 as a pandemic, coronavirus disease 2019 (COVID-19) is a severe respiratory illness. 1 , 2 COVID-19 is highly infective, presenting with a range of symptoms; however, up to 80% of symptomatic COVID-19 infections feature only flu-like symptoms with no complications; 3 advanced complications such as renal or circulatory failure have been reported with severe cases or with other comorbidities or risk factors including old age, hypertension, cardiovascular diseases, or diabetes, especially type 1 diabetes mellitus (T1DM). 4 …”
Section: Introductionmentioning
confidence: 99%
“…Announced by the World Health Organization in January 2020 as a global health emergency and in March 2020 as a pandemic, coronavirus disease 2019 (COVID-19) is a severe respiratory illness. 1 , 2 COVID-19 is highly infective, presenting with a range of symptoms; however, up to 80% of symptomatic COVID-19 infections feature only flu-like symptoms with no complications; 3 advanced complications such as renal or circulatory failure have been reported with severe cases or with other comorbidities or risk factors including old age, hypertension, cardiovascular diseases, or diabetes, especially type 1 diabetes mellitus (T1DM). 4 …”
Section: Introductionmentioning
confidence: 99%
“…As a result of these observations, Treg cells may potentially play a role in assisting with SARS-CoV-2 recovery. However, some conflicting studies reported that a reduction in Treg cells and lower expressions of FOXP3, TGF-β, and IL-10 were present in patients with severe SARS-CoV-2 infection [ 45 , 46 , 47 ]. Therefore, more research is required for the role of Treg cells.…”
Section: T Cell Subsets and Surface Markers Change During Sars-cov-2 ...mentioning
confidence: 99%
“…Hypertension increases the T cell populations and inflammatory cytokine secretion of tumor necrosis factor TNFα, IFNγ, and IL-17A [ 100 , 101 ]. However, one study indicates that there was no difference in T cell populations between hypertensive patients and healthy people [ 47 ]. T cells in hypertensive patients displayed senescence phenotypes with lowered co-expression of CD27 and CD28, resulting in difficulty protecting against viral infections [ 102 ].…”
Section: T Cells’ Response To Comorbidities—diabetes Mellitus Asthma ...mentioning
confidence: 99%
“…In healthy individuals, the innate immune system serves as the initial defense against most infectious signals. It achieves this by orchestrating a protective inflammatory response that evolves through various stages, starting from initiation and full-blown inflammation to resolution and the restoration of tissue integrity [1]. Within the fully active immune system, macrophages, which originate from monocytes, act as phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%